The carnival: ladybird key words reading scheme - Murray, W.; Aitchison, Martin (Ladybird Loughborough, 1997)
The carnival is a vibrant celebration filled with colorful parades, thrilling rides, and festive games, creating a joyful atmosphere for people of all ages. It's a time for community bonding, delicious food, and unforgettable entertainment.